Ductile behavior of polyethylene fibre reinforced geopolymer composite - Shaikh, Faiz; Ronnie, Z. (2017)
© The Authors, published by EDP Sciences, 2017. This paper presents the effects of various volume fractions of polyethylene (PE) fibres of 0.5%, 1%, 1.5% and 2% on tensile, flexure and compressive behavior of PE fibres reinforced geopolymer composites (PE-FRGC). Results show that the 1% PE fibre by volume is the optimum fibre volume fraction for fly ash geopolymer composite, which exhibit superior strain and deflection hardening behavior in uni-Axial tension and three-point bending, respectively. Results also show that the compressive strength of the composites decreases with increase in volume fractions of PE fibre. The fibre surface examination of PE fibre in the gopolymer matrix using scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) revealed no significant damage of PE fibre in the alkaline geopolymer matrix.